Analisis Semiotika Makna Simbolisme Kemuhammadiyahan dalam Lirik Lagu “Indonesia Raya” Satu Stanza - Wijaya, Fauzi Adi; Suroso, Eko (Proceedings Series on Social Sciences & Humanities, 2024)
Semiotic analysis of the lyrics of one stanza of the song "Indonesia Raya" reveals that this song is not just a musical representation but also a symbol that is rich in meaning. One of the meanings contained is the symbolism of Muhammadiyah, which reflects the values of Muhammadiyah in developing Indonesian society and nation. This research was conducted with the aim of carrying out a semiotic analysis of the lyrics of one stanza of the song "Indonesia Raya" in order to reveal the meaning of Muhammadiyah symbolism. The main aim of this research is to highlight and understand more deeply the hidden meanings in the lyrics of the national song and to relate them to the values and mission of da'wah that Muhammadiyah upholds in developing Indonesian society and nation. The approach used is qualitative with semiotic analysis methods to reveal the meaning of the signs or symbols contained in a text. The results of the research stated that it was found that the lyrics of the song "Indonesia Raya" in one stanza reflected strong symbolism related to Muhammadiyah values. This is especially visible in the use of words such as "my homeland" and "Indonesia my nationality," which emphasize deep emotional ties and national identity. The song also expresses the spirit of fighting and independence through phrases such as "build the soul" and "build the body," reflecting the importance of development in all aspects of life. Apart from that, the song lyrics also reflect Islamic values such as love of the homeland and gratitude to Allah SWT. This shows that the song "Indonesia Raya" is not only a symbol of national pride and identity for the Indonesian people, but also contains deep meaning related to the mission of da'wah and Muhammadiyah values, strengthening awareness of unity, independence and Islamic values in the world. Indonesian society.